The retrospective assessment of childhood attention deficit hyperactivity disorder in adults: Reliability and validity of the Italian version of the Wender Utah Rating Scale - Fossati, Andrea; Di Ceglie, Antonella; Acquarini, Elena; Donati, Deborah; Donini, Michela; Novella, Liliana; Maffei, Cesare (Comprehensive psychiatry, 2001)
To assess the reliability and validity of the Wender Utah Rating Scale (WURS), 759 Italian undergraduate students were administered the Italian version of the WURS. In this sample, the WURS showed good internal consistency reliability (Cronbach alpha = .888). Both 1-week ( r = .981, P < .001) and 2-month ( r = .924, P < .001) retest reliabilities were satisfactory. The mother/subject agreement on the WURS total score was large: intraclass r = .883, P < .001. The principal component (PC) analysis showed the presence of three positively correlated first-order PCs, and one second-order PC. This PC structure of the WURS was replicated in an independent sample of 300 consecutively admitted psychiatric inpatients and outpatients. Finally, in a sample of 132 secondary school students, the WURS showed a moderate correlation with the Conners Abbreviated Parent and Teacher Questionnaire (CAPTQ): r = .307, P < .001. In this sample, the WURS total score was negatively correlated with school performance (rho = −.460, P < .001) and conduct (rho = −.293, P < .005) indexes.